Natural Resources and Violent Conflict: Options and Actions (Ian Bannon and Paul Collier, eds.) - Lopez Wui, Ma. Glenda (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Review of Natural Resources and Violent Conflict: Options and Actions, edited by Ian Bannon and Paul Collier.
Keywords: Natural Resources; Violence; Conflict